2020
DOI: 10.3390/pharmaceutics12080753
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Catheter Movement Affects Dye Dispersal Volume in Agarose Gel Brain Phantoms

Abstract: The standard of care for treatment of glioblastoma results in a mean survival of only 12 to 15 months. Convection-enhanced delivery (CED) is an investigational therapy to treat glioblastoma that utilizes locoregional drug delivery via a small-caliber catheter placed into the brain parenchyma. Clinical trials have failed to reach their endpoints due to an inability of standard catheters to fully saturate the entire brain tumor and its margins. In this study, we examine the effects of controlled catheter movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…This can be accomplished in a similar method presented by Orozco et al 43,44 It should also be noted that the model presented here utilizes material properties based on agarose gel and indigo carmine dye in order to validate the model with experimental results conducted in agarose. However, despite its common use as a surrogate to brain tissue, 23,25,26,[55][56][57][58][59] the homogeneous nature of agarose cannot replicate the true heterogeneous and non-isotropic features of brain tissue including blood vessels and ventricles which are known to distort the dispersal volume shape. 60…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be accomplished in a similar method presented by Orozco et al 43,44 It should also be noted that the model presented here utilizes material properties based on agarose gel and indigo carmine dye in order to validate the model with experimental results conducted in agarose. However, despite its common use as a surrogate to brain tissue, 23,25,26,[55][56][57][58][59] the homogeneous nature of agarose cannot replicate the true heterogeneous and non-isotropic features of brain tissue including blood vessels and ventricles which are known to distort the dispersal volume shape. 60…”
Section: Discussionmentioning
confidence: 99%
“…25 We have recently shown that controlled catheter retraction at a rate of 0.25 mm/min can result in an increase in V d by 50% in an agarose gel model. 26 Additionally, we have shown that the use of constant pressure infusions coupled with controlled catheter retraction can result in an increase in V d of 94% and 143% with 0.25 and 0.5 mm/min catheters, respectively. 27 Our objective is to use a computational model to parametrically understand the role of catheter retraction rate on the overall efficacy of controlled catheter movement in CED infusions.…”
Section: Introductionmentioning
confidence: 87%
“…The continuous retraction and intermittent insertion protocols showed significantly higher volumes of distribution than traditional stationary catheters, which were found to have greater backflow and lower forward flow distances. This highlights how tumor coverage can be improved by using dynamic catheters 68 . Apart from infusate reflux, cerebral catheters can also become obstructed during chronic CED.…”
Section: Hardware Infusion Technique and Long-term Convection Enhanced Deliverymentioning
confidence: 92%
“…The continuous retraction and intermittent insertion protocols showed significantly higher volumes of distribution than traditional stationary catheters, which were found to have greater backflow and lower forward flow distances. This highlights how tumor coverage can be improved by using dynamic catheters [ 73 ]. Apart from infusate reflux, cerebral catheters can also become obstructed during chronic CED.…”
Section: Limitations and Recent Developments In The Preclinical Settingmentioning
confidence: 99%